Bare Flesh and Sticky Milk: An Affective Conflict Over Public Breastfeeding - Lehto Mari (Sage Journals, 2022)
On New Year’s Day 2016, a photograph of a breastfeeding woman taken by a Finnish celebrity sparked a social media debate over mothers nursing in public. By analyzing Instagram posts and a discussion forum thread, this article explores the affective body politics involved in this short-lived yet intense social media debate. It examines the power of hashtags and images in mobilizing motherhood as a site of political agency. Concurrently, it investigates how social media users negotiated the appropriate public presentations of the female body and how the celebrity’s gayness became an object of negative affect. The analysis of the incident makes visible how social norms concerning motherhood and heteronormativity are articulated in social media. It also demonstrates how affect sticks to images, texts, and bodies and becomes a binding force in social media discussions concerning them. The article argues that Instagram’s hashtag practices facilitated affective engagement for those following #teriniitti. It further argues that the affective dynamics of the case demonstrate how affective intensities stick on gay bodies and lactating bodies as objects of disgust, fascination, and desire.